Medical Students Are Not Essential Workers: Examining Institutional Responsibility During the COVID-19 Pandemic. (August 2020) - Menon, Anitha; Klein, Edwin J.; Kollars, Kate; Kleinhenz, Alissa L.W.
Abstract : In light of the evolving COVID-19 pandemic, the Association of American Medical Colleges (AAMC) and Liaison Committee on Medical Education (LCME) released a joint statement in March 2020 recommending an immediate suspension of medical student participation in direct patient contact. As graduating medical students who will soon begin residency, the authors fully support this recommendation. Though paid health care workers, like residents, nurses, and environmental services staff, are essential to the management of COVID-19 patients, medical students are not. Students' continued involvement in direct patient care will contribute to SARS-CoV-2 exposures and transmissions and will waste already limited personal protective equipment. By decreasing nonessential personnel in health care settings, including medical students, medical schools will contribute to national and global efforts to "flatten the curve." The authors also assert that medical schools are responsible for ensuring medical student safety. Without the protections provided to paid health care workers, students are uniquely disadvantaged within the medical hierarchy; these inequalities must be addressed before medical students are safely reintegrated into clinical roles. Although graduating medical students and institutional leadership may worry that suspending clinical rotations might prevent students from completing graduation requirements, the authors argue the ethical obligation to "flatten the curve" supersedes usual teaching responsibilities. Therefore, the authors request further guidance from the LCME and AAMC regarding curricular exemptions/alternatives and adjusted graduation timelines. The pool of graduating medical students affected by this pause in direct patient contact represents a powerful reserve, which may soon need to be used as the COVID-19 pandemic continues to challenge the U.S. health care infrastructure.